2017
DOI: 10.1038/bmt.2017.235
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics of torque teno virus plasma DNA load shortly after engraftment predicts the risk of high-level CMV DNAemia in allogeneic hematopoietic stem cell transplant recipients

Abstract: Monitoring Torque teno virus (TTV) DNA load helps to estimate the risk of opportunistic infections in solid organ transplant recipients. We investigated whether the early kinetic pattern of plasma TTV DNA load after allogeneic hematopoietic stem cell transplantation (allo-HSCT) associates with subsequent CMV and EBV DNAemia. This study included 71 allo-HSCT patients. We found that the area under the curve (AUC) for log TTV DNA loads quantified by days 20 and 30 after transplantation (TTV DNA load AUC), was sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
63
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(77 citation statements)
references
References 36 publications
11
63
3
Order By: Relevance
“…14,39-41 We observed a direct correlation, although weak, between recipient age and plasma DNA loads, in line with previous studies performed in healthy adults. 19, 36 We did not replicate, however, such findings since the use of ATG as induction therapy in our cohort was associated with higher viral loads and lower doubling viral times during the first posttransplant months. 9 Both findings would support the immunosuppression, we observed a negative correlation between plasma loads and CD3+, CD4+, and CD8+ T cell counts assessed at months 1 and 3.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…14,39-41 We observed a direct correlation, although weak, between recipient age and plasma DNA loads, in line with previous studies performed in healthy adults. 19, 36 We did not replicate, however, such findings since the use of ATG as induction therapy in our cohort was associated with higher viral loads and lower doubling viral times during the first posttransplant months. 9 Both findings would support the immunosuppression, we observed a negative correlation between plasma loads and CD3+, CD4+, and CD8+ T cell counts assessed at months 1 and 3.…”
Section: Discussioncontrasting
confidence: 65%
“…6 Torque teno virus (TTV), first isolated in 1997 from a Japanese patient with posttransfusion hepatitis, 7 constitutes the prototype member within the Anelloviridae family. 10,11 Immunosuppressive therapy for solid organ transplantation (SOT), 12-15 postengraftment phase after allogeneic hematopoietic stem-cell transplantation, [16][17][18][19] or CD4 + T cell depletion in human immunodeficiency virus (HIV) infection 20,21 lead to an evident increase in alphatorquevirus DNA loads that would in turn correlate with the overall amount of immunosuppression. TTV infection is thought to be acquired in childhood via multiple routes (transplacental, respiratory, fecal-oral, or transfusion) and reaches a prevalence as high as 90% among the adult population.…”
Section: Introductionmentioning
confidence: 99%
“…In the setting of allogeneic stem cell transplantation, Albert et al showed an inverse association between TTV viremia and CMV infection, whereas no overall correlation was found between TTV DNA and CMV DNA. (21) Wohlfarth et al, in turn, showed a direct link between TTV DNA and CMV infection, as well as a linear correlation between the DNA of both viruses. (22) In the context of solid organ transplantation, a direct association between TTV and CMV infection has been reported in kidney transplantation, (19) whereas a report on lung recipients found no relationship.…”
Section: Discussionmentioning
confidence: 96%
“…Regarding the interaction between CMV and TTV, conflicting results have been reported in the literature. In the setting of allogeneic stem cell transplantation, Albert et al showed an inverse association between TTV viremia and CMV infection, whereas no overall correlation was found between TTV DNA and CMV DNA . Wohlfarth et al, in turn, showed a direct link between TTV DNA and CMV infection, as well as a linear correlation between the DNA of both viruses .…”
Section: Discussionmentioning
confidence: 99%
“…PCR amplification and amplicon detection were done on the ABI Prism 7500 system (PE Biosystems, Foster City, CA). Sample processing for TTV DNA quantitation on plasma samples was previously described . The limit of quantitation of the PCR assay was around 25 copies/mL and the limit of detection, approximately 10 copies/mL (75% repeatability).…”
Section: Methodsmentioning
confidence: 99%